2019
DOI: 10.1155/2019/8653247
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the Axial Load Capacity of RC Columns Strengthened with Steel Jacketing under Preloading Based on FE Simulation

Abstract: Reinforced concrete (RC) columns often require consolidation or rehabilitation to enhance their capacity to endure the loads applied. This paper aims at studying the conduct and capacity of RC square columns, those reinforced with steel jacketing under static preloads. For this purpose, a three-dimensional model of finite element (FE) is devised mainly to investigate and analyze the effect of this case. The model was tested and adjusted to ensure its accuracy using the previous experimental results obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The present study aimed to investigate the behaviour of equal and unequal single-angle steel members using finite element (FE) simulations and analysis, which are currently widely used to analyze steel structural elements and have been shown to give highly accurate results [20][21][22]. The single angles are connected through one leg by welding connections under different end deformations, where the deformation is controlled in the two directions perpendicular to the load axis.…”
Section: Figure 1 Distribution Of Stresses On a Steel Single-angle Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study aimed to investigate the behaviour of equal and unequal single-angle steel members using finite element (FE) simulations and analysis, which are currently widely used to analyze steel structural elements and have been shown to give highly accurate results [20][21][22]. The single angles are connected through one leg by welding connections under different end deformations, where the deformation is controlled in the two directions perpendicular to the load axis.…”
Section: Figure 1 Distribution Of Stresses On a Steel Single-angle Sectionmentioning
confidence: 99%
“…The engineering stress-strain relationship and elastic modulus of the steel elements, which are measured experimentally by tension tests, are acquired from a previously published work [7]. The average engineering stress-strain relationship of the tension test results [7] is applied to FE modeling, as shown in Table 1, with elastic modulus is set to 203 GPa, and a Poisson's ratio of 0.3 is applied [20][21][22]. The model is divided into small elements with l×w×h of 10 ×5 ×5 mm as a maximum size.…”
Section: Steel Modelling and Characteristicsmentioning
confidence: 99%
“…The steel sheets integrated into the FE numerical simulation models were expected to have linear elasticity. The elastic modulus and the stress-strain engineering relationships that depend upon the experimental test specimens which were done in this research and the Poisson ratio of 0.3 was applied [14,15]. The maximum size of the meshing elements was taken as being 1 mm in length, 1 mm in width, and 1 mm in height.…”
Section: Experimental Test Specimensmentioning
confidence: 99%
“…Nowadays, finite-element FE modeling and simulation techniques are widely used in research involving structural analysis and design, especially of structural steel elements [14,15]. In some research, FE modeling techniques are often used to expand the limitations of the experimental testing analysis, because of the difficulty of implementation or high cost, and are also used to investigate the different parameters which that affect the problem study.…”
Section: Introductionmentioning
confidence: 99%
“…The review was structured according to the method of strengthening, and indicated that none of these studies considered the effect of the presence of a preload or pre-cracks in the RC columns on the strengthening process. Some numerical studies considered the effect of preloading on strengthening with steel angle jacketing [40][41][42], and demonstrated that preloading greatly impacts the efficiency of the strengthening of RC columns according to the preload on the column. Therefore, in this study, RC columns were strengthened with RC jacketing after cracks formed on the sides of the columns, to determine their effect on the efficiency of strengthening.…”
Section: Introductionmentioning
confidence: 99%